Daily weather types in February-June (1979-2016) and temperature variations in tropical North Africa. - Moron, Vincent; Oueslati, Boutheina; Pohl, Benjamin; Janicot, Serge (Journal of Applied Meteorology and Climatology, 2018)
International audience This study investigates to what extent weather types (WTs) computed over tropical North Africa and the tropical North Atlantic Ocean (40°W–40°E, 0°–30°N) are relevant for documenting intraseasonal and interannual temperature variability in tropical North Africa (west of 37°E, 2°–27°N). Nine WTs are extracted by using clustering analysis of the daily anomalies of sea level pressure and low-level 925-hPa winds from two reanalyses (NCEP–DOE and ERA-Interim) from 1979 to 2016. The analyses are carried out separately for February–March and for April–June, when temperatures reach their annual peak across most of the region. The WT patterns mix the effects of different multiscale phenomena, including the extratropical Rossby waves that travel on the northern edge of the domain (and are partly related to the North Atlantic Oscillation), the Madden–Julian oscillation, and Kelvin waves in the subequatorial zone. For each WT, warm (cold) minimum (TN) and maximum (TX) daily temperature anomalies tend to be systematically located east of cyclonic (anticyclonic) low-level circulation anomalies associated with the WT patterns. By modulating the greenhouse effect, the water vapor anomalies exert a major influence, leading to warm (cold) TX and TN anomalies associated with moister (drier) air, through advection from the tropical Atlantic or equatorial latitudes (the Sahara or northern latitudes) toward tropical North Africa. WTs are also useful for monitoring interannual variability of TX/TN anomalies mostly north of 10°N in February–March, even if they greatly underestimate the long-term warming trend. Most WTs significantly raise or lower the probability of regional-scale heat peaks, defined as the crossing of the 90th percentile of daily TX or TN.